The ethics of corporate lobbying - Dobson, Wendy (My University, 2016)
This research sought to defend the proposition that not only do corporations have a moral right to lobby, corporations also have a moral duty to influence public policy through lobbying. The research has considered the ethics of corporate lobbying within the context of the extent literature in Business Ethics and from a South African perspective. An argument for corporate moral personhood has been advanced as the basis for a corporation’s moral right to lobby. The rights and duties of corporations as citizens have also been considered, and a case has been made for a normative theory of corporations as political actors with an associated moral obligation to seek to influence public policy to promote public interests. A set of ethical principles to guide responsible lobbying has been articulated as a morally justified basis for restricting a corporation’s moral right to lobby which arises from its status as a type of moral person to ensure that the power of corporations is harnessed in service of society.
A Research Report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts, Applied Ethics for Professionals Johannesburg, 2016
Keywords: Business ethics--South Africa; Professional ethics--South Africa; Lobbying--South Africa; Public policy--South Africa